Seasonal Cycle in Sea Level Across the Coastal Zone - Rui M. Ponte; Michael Schindelegger (Earth and Space Science)
Abstract Data from tide gauges and satellite altimeters are used to provide an up‐to‐date assessment of the mean seasonal cycle in sea level (ζ) over most of the global coastal ocean. The tide gauge records, where available, depict a ζ seasonal cycle with complex spatial structure along and across continental boundaries, and an annual oscillation dominating over semiannual variability, except in a few regions (e.g., the northwestern Gulf of Mexico). Comparisons between tide gauge and altimeter data reveal substantial root‐mean‐square differences and only slight improvements in agreement when using along‐track data optimized for coastal applications. Quantification of the uncertainty in the altimeter products, inferred from comparing gridded and along‐track estimates, indicate that differences to tide gauges partly reflect short‐scale features of the seasonal cycle in proximity to the coasts. We additionally probe the ζ seasonal budget using satellite gravimetry‐based manometric estimates and steric terms calculated from the World Ocean Atlas 2023. Focusing on global median values, the sum of the estimated steric and manometric harmonics can explain ∼ 65% (respectively 40%) of the annual (semiannual) variance in the coastal ζ observations. We identify several regions, for example, the Australian seaboard, where the seasonal ζ budget is not closed and illustrate that such analysis is mainly limited by the coarse spatial resolution of present satellite‐derived mass change products. For most regions with a sufficiently tight budget closure, we find that although the importance of the manometric term generally increases with decreasing water depth, steric contributions are non‐negligible near coastlines, especially at the annual frequency.